Social Media Marketing and Marketing Performance: The Mediating Role of Customer Engagement - Andhi Febisatria; Aris Baharuddin; Leonardo Davidsi Sipayung; Sovia Rosalin (PINISI Discretion Review, 2026)
This study investigates relationships among Social Media Marketing, Customer Engagement, and Marketing Performance using a PLS-SEM approach. Measurement model assessment confirms that all constructs meet required validity and reliability criteria, providing a robust foundation for structural analysis. Empirical findings indicate that Social Media Marketing has a positive and significant effect on Marketing Performance, showing that social media–based activities enhance SME performance through wider market reach and more effective marketing communication. Results also reveal a significant positive influence of Social Media Marketing on Customer Engagement, highlighting the importance of content quality, interaction, and communication intensity in encouraging active customer involvement. Evidence further demonstrates that Customer Engagement positively affects Marketing Performance and significantly mediates the relationship between social media marketing and performance outcomes. Overall findings emphasize that marketing performance optimization depends on social media strategies that prioritize continuous and meaningful customer engagement.